Therapeutic Activity of a Topical Formulation Containing 8-Hydroxyquinoline for Cutaneous Leishmaniasis - Sarah Kymberly Santos de Lima; Ítalo Novaes Cavallone; Dolores Remedios Serrano; Brayan J. Anaya; Aikaterini Lalatsa; Márcia Dalastra Laurenti; João Henrique Ghilardi Lago; Dalete Christine da Silva Souza; Gabriela Pustiglione Marinsek; Beatriz Soares Lopes; Renata de Britto Mari; Luiz Felipe Domingues Passero (MDPI AG, 2023)
Cutaneous leishmaniasis exhibits a wide spectrum of clinical manifestations; however, only a limited number of drugs are available and include Glucantime® and amphotericin B, which induce unacceptable side effects in patients, limiting their use. Thus, there is an urgent demand to develop a treatment for leishmaniasis. Recently, it was demonstrated that 8-hydroxyquinoline (8-HQ) showed significant leishmanicidal effects in vitro and in vivo. Based on that, this work aimed to develop a topical formulation containing 8-HQ and assess its activity in experimental cutaneous leishmaniasis. 8-HQ was formulated using a Beeler base at 1 and 2% and showed an emulsion size with a D50 of 25 and 51.3 µm, respectively, with a shear-thinning rheological behaviour. The creams were able to permeate artificial Strat-M membranes and excised porcine skin without causing any morphological changes in the porcine skin or murine skin tested. In BALB/c mice infected with L. (L.) amazonensis, topical treatment with creams containing 1 or 2% of 8-HQ was found to reduce the parasite burden and lesion size compared to infected controls with comparable efficacy to Glucantime® (50 mg/kg) administered at the site of the cutaneous lesion. In the histological section of the skin from infected controls, a diffuse inflammatory infiltrate with many heavily infected macrophages that were associated with areas of necrosis was observed. On the other hand, animals treated with both creams showed only moderate inflammatory infiltrate, characterised by few infected macrophages, while tissue necrosis was not observed. These histological characteristics in topically treated animals were associated with an increase in the amount of IFN-γ and a reduction in IL-4 levels. The topical use of 8-HQ was active in decreasing tissue parasitism and should therefore be considered an interesting alternative directed to the treatment of leishmaniasis, considering that this type of treatment is non-invasive, painless, and, importantly, does not require hospitalisation, improving patient compliance by allowing the treatment to be conducted.